Russian Language Teachers in the Era of Artificial Intelligence: New Professional Identities - Wang Duo (Вестник Московского Университета. Серия 20: Педагогическое образование)
Background. In the era of AI, teachers of the Russian language face new challenges: technologies are reshaping their professional identity while simultaneously creating opportunities for growth. The study of AI’s impact on the transformation of educators’ roles and their adaptation strategies is of particular importance.